Challenges and Solutions for Labor Law Reform that Strengthens Workers' Rights in Viet Nam - Thuy, Nguyen Thi; Pham, Hoang Huy; Stern, David Regier (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2024)
This study provides a comprehensive analysis of the legal protections for bargaining rights in Vietnam, exploring the impacts of rapid economic development, globalization, and recent legislative reforms. The Đổi Mới reforms of the late 20th century marked a significant shift from a centrally planned economy to a socialist-oriented market economy, leading to substantial changes in Vietnam’s labor laws. These reforms aimed to align Vietnam’s labor regulations with international standards, particularly concerning workers' bargaining rights. Employing a qualitative research approach, this study analyzes the effectiveness of Vietnam’s Labour Code, the role of trade unions, and recent legislative updates through documentary research and expert interviews. Findings highlight both progress and challenges: while legal provisions for collective bargaining and the role of trade unions have seen improvements, significant weaknesses remain in enforcement mechanisms and coverage for informal workers. The research identifies practical issues, including the disparity between formal and informal sectors and the limited independence of trade unions. The study proposes recommendations to enhance bargaining rights protections, such as strengthening enforcement, expanding legal coverage to informal workers, increasing trade union autonomy, and improving legal aid services. These insights aim to inform policymakers, legal practitioners, and labor rights advocates on how to address existing gaps and improve the effectiveness of labor protections in Vietnam. Ultimately, this research contributes to the broader discourse on labor rights in transitioning economies, offering strategies for advancing legal protections in response to ongoing economic and social changes.